RETRACTION: Identification of Occupational Safety and Health Hazards with Job Safety Analysis (JSA) Method for Paper Core Factory Workers - Saputra, Dwi Arwandi Yogi; Perdini, Fitriana Titis; Harjono, Yanti; Savitri, Pritha Maya (Civiliza Publishing, 2025)
This article was withdrawn based on considerations from the editorial team due to double publication.